Analysis of tunnel-induced settlement damage to surface structures - Houlsby, G; Burd, H; Augarde, C (A.A.Balkema, 1999)
Transport developments in cities often involve tunnelling, which inevitably leads to ground movements. These must be carefully predicted if there is a risk of settlement damage to nearby structures. Tunnel-induced settlements may be predicted empirically for greenfield sites, but surface structures modify these movements. Two-dimensional models, often used in practice, neglect the effect of transients as the tunnel is excavated and do not allow realistic models of buildings. Research on a 3-D numerical model of tunnelling is described. This includes a building and a simulation of tunnel construction processes. Interactions between the building and the ground are investigated. Settlement, and structural damage, is studied as the tunnel installation proceeds. An analysis of a building unsymmetrical in plan to the tunnelling direction is presented.